1975
DOI: 10.1083/jcb.64.2.438
|View full text |Cite
|
Sign up to set email alerts
|

Externally disposed plasma membrane proteins. I. Enzymatic iodination of mouse L cells.

Abstract: The enzymatic iodination technique has been utilized in a study of the externally disposed membrane proteins of the mouse L cell. lodination of cells in suspension results in lactoperoxidase-specific iodide incorporation with no loss of cell viability under the conditions employed, less than 3% lipid labeling, and more than 90% of the labeled species identifiable as monoiodotyrosine. 90% of the incorporated label is localized to the cell surface by electron microscope autoradiography, with 5-10% in the centros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
162
0

Year Published

1975
1975
1995
1995

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 346 publications
(166 citation statements)
references
References 64 publications
4
162
0
Order By: Relevance
“…Use of the enzymatic iodination technique to label only the externally disposed membrane proteins provided a reasonable solution to both problems. In the preceding report (16), we demonstrated that monoiodotyrosine (MIT)J a nonreutilisable amino acid (27), represents at least 90% of the iodinated species when intact L cells are labeled with the lactoperoxidase (LPO) system. In addition, 90% of the label has been localized to the plasma membrane after iodination, so any decrease in cell-associated radioactivity with time necessarily represents loss of label from those proteins originally present in the plasma membrane compartment.…”
mentioning
confidence: 99%
“…Use of the enzymatic iodination technique to label only the externally disposed membrane proteins provided a reasonable solution to both problems. In the preceding report (16), we demonstrated that monoiodotyrosine (MIT)J a nonreutilisable amino acid (27), represents at least 90% of the iodinated species when intact L cells are labeled with the lactoperoxidase (LPO) system. In addition, 90% of the label has been localized to the plasma membrane after iodination, so any decrease in cell-associated radioactivity with time necessarily represents loss of label from those proteins originally present in the plasma membrane compartment.…”
mentioning
confidence: 99%
“…1). Lactoperoxidase, a macromolecule of about 150,000 molecular weight, does not cross the lipid bilayer of intact cells, and therefore under appropriate conditions can catalyze the iodination of only externally disposed cell surface proteins (27,28). Individual proteins were classified by molecular weight as determined with molecular weight standards by NaDodSO4/polyacrylamide gel electrophoresis.…”
Section: Resultsmentioning
confidence: 99%
“…Surface labelling.-Subconfluent cultures were surface iodinated according to the method of Hubbard & Cohn (1975). The reaction mixture contained 38 ,tg/ml lactoperoxidase (Sigma, St. Louis, Mo., U.S.A.) 0-6 u/ml glucose oxidase (Sigma type VII) 2-5 mg/ml glucose and 0-125 mCi/ml Na125I carrier-free (Amersham, U.K.) in phosphatebuffered saline (or in Williams's E medium plus FCS).…”
Section: Methodsmentioning
confidence: 99%